771 Levetiracetam Dosing for Seizure Prophylaxis in Neurocritical Care Patients. (April 2023) - Findlay, Matt; Hedges, Ashley; Menacho, Sarah Tamara; Ansari, Safdar; Hawryluk, Gregory W. J.; Davis, Gary; Wolfe, Brianne; Lingenfelter, Erin
Abstract : INTRODUCTION: Levetiracetam has emerged as a safer alternative to phenytoin for seizure prophylaxis in patients presenting with subarachnoid hemorrhage (SAH) or traumatic brain injury (TBI). However, it remains unclear which Levetiracetam dosing regimen is most effective at preventing seizures. METHODS: A retrospective cohort study captured adult patients at a quaternary care center presenting with SAH or TBI who received levetiracetam as a total daily dose (TDD) equivalent to or greater than 1000 mg. The primary outcome was the combined seizure incidence, including clinical and subclinical seizures. RESULTS: Among the 139 patients identified, 49.6% were male, and the mean age was 53 years. For patients receiving 1000 mg TDD levetiracetam, the administration was 500 mg twice daily. For patients receiving >1000 mg TDD, 77/78 patients received 1000 mg twice daily, and the remaining patient received 750 mg twice daily. A higher seizure incidence was observed, 11.5% vs 1.3%, in patients receiving 1000 mg TDD compared with doses >1000 mg TDD, respectively (p = 0.01), despite no difference in examined confounders, including history of alcoholism (14.8% vs. 19.2%, p = 0.49), benzodiazepine use (65.6% vs. 73.1%, p = 0.28), or propofol use (62.3% vs. 62.8%, p = 0.17). No difference in adverse effects were observed (anemia 1.6% vs. 3.8%, p = 0.44; leukopenia 6.6% vs. 9.0%, p = 0.60; thrombocytopenia 1.6% vs. 1.3%, p = 0.86). CONCLUSIONS: Patients may experience a reduced incidence of clinical and electroencephalographic seizures with levetiracetam dosing greater than 1000 mg TDD.